Business as a pivotal actor in the politics of training reform : insights from the case of Germany - Busemeyer, Marius R. [Verfasser] (My University, 2012)
"Often admired by international observers, the German dual training system has come under pressure in recent years because of a persistent lack in training slots for young people. The article addresses the question of how policy makers have reacted to the problems in the training market. Particular attention is paid to the formation of politico-economic coalitions between state actors, business representatives and unions. On the basis of three case studies of recent reforms (or reform attempts), we identify two types of cross-class coalitions: a conservative coalition that aims at maintaining the status quo of the firm-based training regime and a segmentalist coalition promoting the gradual transformation of the system towards a less collective and more firm-centred variety. In both kinds of politico-economic coalitions, business actors play a pivotal role. The reason for the privileged position of business in the politics of training reform is, I argue, a politically constructed dependency of the state and unions on the continued co-operation of business in the provision of training slots. In the conclusion, I discuss the implications of my findings for the debate on the dualization of co-ordinated market economies." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; S 4.1.4 Fonds- und Umlagefinanzierung; Berufsbildungspolitik; Bildungsreform; Berufsbildungssystem; Betriebliche Berufsausbildung; Zweijähriger Ausbildungsberuf; Ausbildungsstellenmarkt; Ausbildungsplatzdefizit; Berufsbildungsgesetz; Ausbildungsplatzabgabe